طرائق جديدة لحل مشاكل البرمجة الخطية الضبابية المتماثلة - صالح, سرمد علوان (Journal of Economics and Administrative Sciences, 2016)
Several authors have used ranking function for solving linear programming problem. In This paper is proposed two ranking function for solving fuzzy linear programming and compare these two approach with trapezoidal fuzzy number .The proposed approach is very easy to understand and it can applicable, also the data were chosen from general company distribution of dairy (Canon company) was proposed test approach and compare; This paper prove that the second proposed approach is better to give the results and satisfy the minimal cost using Q.M. Software